Pengaruh Pendidikan Kesehatan Melalui Media Vidio Terhadap Pengetahuan Tentang Anemia Pada Remaja Putri - Fulatul Anifah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to identify the difference in the level of knowedge of health education with video media about anemia in adolescent girls. Methods: The research design used a quasi experimental one group pre-post test. Respondents were given a pre test before being treated and a post test after thatThe sample was selected by purposive sampling with inclusion and exclusion criteria. The sample size is 31 people.Results: There was an increase in knowledge from 7 to 17 respondents after being given health education through videos. There is a statistical difference in the average level of knowledge of respondents before and after being given health education through vidioConclusion: The level of knowledge of young women about anemia can be increased by providing health education through videos